Etch stop characteristics of SrBi2Ta2O9 thin film by using CeO2 buffer layer - Kwon, YS; Il Shim, S; Kim, SI; Kim, YH; Choi, IH (KOREAN PHYSICAL SOC, 2004)
The etch stop process of SrBi2Ta2O9 (SBT) over CeO2 in Inductively Coupled Plasma Reactive Ion Etching (ICP-RIE) is reported in this paper. The etch stop of ferroelectric thin film on a silicon surface without damage is important for the self-aligned gate structure process in the fabrication of the single-transistor-type ferroelectric random access memory. A high vertical etching angle is also necessary for high integration. We investigated the etch rate of SBT and of Si and CeO2 which were used as a buffer layer to improve the interface between SBT and silicon, with various Ar/Cl-2 gas mixtures, ICP powers and BF bias powers in ICP-RIE. The highest etching selectivity of SBT/CeO2 and SBT/Si was 6.8 and 0.3 respectively. The vertical angle of SBT was 82 degrees. SEM images and XPS surface analyses showed good etch stop characteristics of the buffer layer without damage to the silicon surface.
Keywords: PT/SRBI2TA2O9/CEO2/SIO2/SI STRUCTURE; ELECTRICAL-PROPERTIES; FABRICATION